Utilization of the Palagan Ambarawa Monument as a Historical Learning Resource - Sulistiyanto, Eko (Universitas Negeri Semarang, 2017)
This research is a quantitative experimental design. The population in this study were students of class XI SMA Sudirman Ambarawa Islam. The samples in this study used a simple random sampling design with a pretest - a posttest control group design. Samples were students of class XI IPS 2 as the control class and those of class XI IPS 1 as the experimental class. This research uses data collection methods, such as a questionnaire and documentation. The data analysis technique used in this research is descriptive statistics. From the results of the study, it can be seen there is a difference between interest in learning the history of experimental class learning treated using Ambarawa Theater Monument as a learning resource and control classes not given special treatment. A learning model with a visit to historical places should be implemented by teachers as an alternative to learning history so that students do not feel bored and are motivated to study history harder.